The Role of Financial Literacy in Enhancing Entrepreneurial Competencies Among Business Education Students in Nigerian Colleges of Education - Kasimu, Aminu; Jamilu, Usman Mohammed (EDUMALSYS Journal of Research in Education Management, 2024)
This study explores the role of financial literacy in enhancing the entrepreneurial competencies of Business Education students in Nigerian Colleges of Education. A descriptive survey research design was employed, involving a sample of 220 respondents from various institutions. Data were collected using a structured questionnaire, focusing on the levels of financial literacy, the relationship between financial literacy and entrepreneurial competencies, and the influence of financial literacy on students' ability to identify business opportunities and manage finances. The findings revealed a moderate level of financial literacy among students, with significant positive correlations between financial literacy and entrepreneurial competencies. Specifically, financial literacy was found to improve students' capacity to identify business opportunities and enhance their financial management skills. The study concludes that integrating comprehensive financial literacy training into the Business Education curriculum is essential for equipping students with the necessary skills to succeed as entrepreneurs. Recommendations for educational institutions include developing targeted financial literacy programs, organizing workshops, promoting certification, and partnering with financial institutions to provide practical financial knowledge.